The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.21608/jcese.2022.269495
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Properties of Weighted Shanker Distribution

Abstract: In this article we introduce and investigate the weighted Shanker distribution, a weighted version of Shanker's (2015) Shanker distribution. To obtain the form of the weighted Shanker distribution, which is shown as a generalization of the Shanker distribution, a special non-negative weight function is considered. The statistical properties of the weighted Shanker distribution are investigated. We propose a maximum likelihood method for estimating the weighted version's unknown parameter. To observe the patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…For more information about simulation study see [10], [11], and [12]. Hence, we assess the performance of the MLE using correct initial values and an obvious algorithm as follows:…”
Section: Simulationmentioning
confidence: 99%
“…For more information about simulation study see [10], [11], and [12]. Hence, we assess the performance of the MLE using correct initial values and an obvious algorithm as follows:…”
Section: Simulationmentioning
confidence: 99%
“…Oguntunde [8] presented the exponentiated weighted exponential distribution (EWED) and discussed its statistical properties. Helal et al [9] discussed statistical properties of weighted Shanker distribution. MLE and method of moments (MOM) were used for estimating the parameters of the model.…”
Section: Introductionmentioning
confidence: 99%
“…In 2021, Mahmood et al [19] published an enlarged Cosine generalised family of distributions for dependability modelling: characteristics and applications with simulation analysis, and Muse et al [20] suggested a new flexible form of the loglogistic distribution. Citations [5], [17], and [6] in 2022 explored a family of produced distributions with applications.…”
Section: Introductionmentioning
confidence: 99%